Writing under the 'Auto/biographical Demand' in Deborah Feldman’s Unorthodox (2012) and Exodus (2015) - Szidonia Haragos (European Journal of Life Writing)
This article offers a reading of Deborah Feldman’s memoir sequel, Unorthodox: The Scandalous Rejection of My Hasidic Roots (2012) and Exodus: A Memoir (2015), through the lens of what Leigh Gilmore calls 'the auto/biographical demand'. It argues that Feldman writes under the 'auto/biographical demand' as the grandchild of Hungarian Holocaust survivors and redeploys the inherited story of gendered suffering during the Holocaust in order to reconfigure her own Jewish American identity. I employ Gilmore’s concept to reflect upon the writing of the self in Feldman’s memoir sequel in terms of narrative entanglement, postmemory, and third generation transmission of collective trauma. In addition, the article reflects on Feldman’s text as an echo chamber of the profoundly controversial Kastner affair during the Holocaust in Hungary and its transatlantic reverberations.